Volatilome Analysis for Differentiating Terroir Expression: A Case Study of Three Wineries in a Limestone-Rich, Warm-Climate Region - José Miguel Fuentes-Espinosa; Raquel Muñoz-Castells; Jaime Moreno-García; Teresa García-Martínez; Juan Carlos Mauricio; Juan Moreno (Molecules)
This study investigated young white wines produced during the 2021 and 2022 vintages from Pedro Ximénez grapes cultivated in three different terroirs within a high-quality production zone. The general oenological parameters were significantly influenced by vintage and terroir (p ≤ 0.001), with ethanol and reducing sugars specifically affected by the terroir and its interaction with the vintage. Multivariate analysis of major and minor volatile compounds enabled the characterization of terroir-specific volatile profiles. However, principal component analysis (PCA) grouped samples by vintage rather than terroir. Ethyl esters of medium- and long-chain fatty acids and certain acetates of higher alcohols were the most discriminant volatiles and were proposed as key compounds for differentiating wines by terroir and vintage. These findings underscore the influence of the terroir on the volatilome and support its relevance in defining wine typicity and quality.